1993
DOI: 10.1007/bf02185412
|View full text |Cite
|
Sign up to set email alerts
|

Linear models relating xanthophylls and lumen acidity to non-photochemical fluorescence quenching. Evidence that antheraxanthin explains zeaxanthin-independent quenching

Abstract: Zeaxanthin has been correlated with high-energy non-photochemical fluorescence quenching but whether antheraxanthin, the intermediate in the pathway from violaxanthin to zeaxanthin, also relates to quenching is unknown. The relationships of zeaxanthin, antheraxanthin and ΔpH to fluorescence quenching were examined in chloroplasts ofPisum sativum L. cv. Oregon andLactuca sativa L. cv. Romaine. Data matrices as five levels of violaxanthin de-epoxidation against five levels of light-induced lumen-proton concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
3
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(184 citation statements)
references
References 28 publications
10
168
3
3
Order By: Relevance
“…It is also possible that antheraxanthin is involved in the quenching as early antheraxanthin levels were similar across untreated, DTT-treated, and DTSSP-treated thylakoids ( Figure S3b). 37,42 It is noteworthy that a dip in the signal was observed at 5 min in both fluorescence and TA snapshot data. This suggests that the CT quenching is still important in the early stages of NPQ even with reduced VDE activity.…”
Section: * S Supporting Informationmentioning
confidence: 89%
“…It is also possible that antheraxanthin is involved in the quenching as early antheraxanthin levels were similar across untreated, DTT-treated, and DTSSP-treated thylakoids ( Figure S3b). 37,42 It is noteworthy that a dip in the signal was observed at 5 min in both fluorescence and TA snapshot data. This suggests that the CT quenching is still important in the early stages of NPQ even with reduced VDE activity.…”
Section: * S Supporting Informationmentioning
confidence: 89%
“…However, q,-quenching can occur in the absence of zeaxanthin [ 141, and more recently, Horton and colleagues have shown that the presence of zeaxanthin in leaves preilluminated before rapid preparation of chloroplasts correlated strongly with an enhanced level of q,-quenching [12], which otherwise shows properties similar to those in the absence of zeaxanthin. Gilmore and Yamamoto [45] showed that the amplitude of quenching was proportional to the sum of antheraxanthin and zeaxanthin, and suggested that the de-epoxidation products are necessary for quenching.…”
Section: Evidence For a Role For The Minor Light-harvesting Complexesmentioning
confidence: 99%
“…A number of laboratories have looked at the distribution of carotenoid pigments among the different light-harvesting chlo- rophyll protein complexes [29,44,45]. Violaxanthin, the precursor of antheraxanthin and zeaxanthin in the xanthophyll cycle, partitioned predominantly into the minor complexes, CP29, CP26 and CP24.…”
Section: Evidence For a Role For The Minor Light-harvesting Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The linkage between the acidification of the thylakoid lumenal space and the biophysical mechanism of Chl fluorescence quenching, however, is complex and much of it remains to be understood [l]. The most concise picture indicates that NPQ correlates linearly with the product of the lumen proton concentration and the combined concentrations of the monoepoxide antheraxanthin (Anth) and epoxide-free zeaxanthin (Zeax) [4]. The biochemistry of the interconversions of Violaxanthin (Viol), Anth and Zeax in the xanthophyll cycle has been extensively characterized using isolated chloroplast systems [5] and is outlined schematically as follows: …”
Section: Introductionmentioning
confidence: 99%